CONTRIBUTION OF NICHE TOURISM IN THE CENTRAL ASIAN TOURISM MARKET - Radjabova Kristina Anatolevna (Scholars Digest Publishing, 2024)
Niche tourism refers to tailoring a tourism product to the needs of a certain audience (market segment). Locations with unique specialist products might establish and market themselves as niche tourism destinations. Niche tourism, through image development, enables places to differentiate their tourism products and compete in an increasingly competitive and crowded tourism market. Academic literature has given little thought to the role and positioning of niche tourism offerings. The niche tourism life cycle reveals that niche products have varying impacts, marketing obstacles, and contributions to the Central Asian tourism market development.
Keywords: Tourism, travel, tourist, niche tourism, tourism market, tourism development.